Reconditioning and Repair of Electrical Installation at Mushola Al Mujahidin – Pengasinan Depok: Rekondisi Perbaikan Instalasi Listrik di Mushola Al Mujahidin – Pengasinan Depok - Arif Falah; Sunardi Sunardi; Irawati Irawati; Roby Gunawan; Ahmad Faozan; Nabil Muhamad Fauz; Zanuar Iskandar; Siti Rokhmanila (Institut Riset dan Publikasi Indonesia, 2025)
Indonesia is the country with the largest Muslim population in the world. In Islam, religious activities are carried out in places of worship called mosques or prayer rooms (mushola), and these activities require supporting facilities—one of which is the use of electrical energy. A good electrical installation is regulated in the 2020 Indonesian Electrical Installation Standards (PUIL 2020) to ensure safety, reliability, and environmental friendliness.The Pengabdian kepada Masyarakat (PkM) activity conducted by the Electrical Engineering Department of Pamulang University involved reconditioning and repairing the electrical installation at Mushola Al Mujahidin in Pengasinan, Depok. The aim was to improve the safety and comfort of the local residents in using electricity and electrical equipment. This activity also included an educational outreach program.The repairs covered replacing electrical cables, installing proper electrical protection (MCB), repairing lights, water pumps, and audio equipment, as well as conducting socialization sessions on basic electrical knowledge and installation, safety in using and installing electrical systems, and careers in the electrical field.